The Influence of Islamic Cultural History (SKI) and Aqidah Akhlak Learning on Enhancing Understanding of Religious Moderation - Neng Liah Sapliah; Fitriyani Kosasih (Journal of Science and Education (JSE), 2025)
This study examines the influence of integrated learning in the subjects of Islamic Cultural History (SKI) and Aqidah Akhlak on enhancing students’ understanding of religious moderation at MTs Nurul Falah Bandung. Using a mixed-method sequential explanatory approach, data were collected through Likert-scale pre-tests and post-tests as well as semi-structured interviews. The results of the paired t-test showed a significant increase in the average scores of religious moderation understanding: cognitive dimension rose from 3.05 to 3.98, affective from 3.18 to 4.04, and conative from 3.13 to 4.00, with p < 0.001. Regression analysis indicated that the intervention contributed β = 0.62 with R² = 0.58. Qualitative findings revealed that the integration of historical narratives and moral values strengthened students’ tolerant, empathetic, and reflective attitudes toward differences. The study concludes that contextually integrated SKI and Aqidah Akhlak learning is effective in fostering the values of religious moderation and can serve as a character education model in madrasahs.